Zika virus-like particles (VLPs) produced in insect cells - de Mello, Renata Gois; Bernardino, Thaissa Consoni; Guardalini, Luis Giovani Oliveira; Astray, Renato Mancini; Antoniazzi, Marta Maria; Jared, Simone Gonçalves Silva; Núñez, Eutimio Gustavo Fernández; Jorge, Soraia Attie Calil (Frontiers in Pharmacology, 2023)
Introdutcion: The Zika virus (ZIKV) infections are a healthcare concern mostly in the Americas, Africa, and Asia but have increased its endemicity area beyond these geographical regions. Due to the advances in infections by Zika virus, it is imperative to develop diagnostic and preventive tools against this viral agent. Virus-like particles (VLPs) appear as a suitable approach for use as antiviral vaccines. Methods: In this work, a methodology was established to produce virus-like particles containing the structural proteins, C, prM, and E of Zika virus produced in insect cells using the gene expression system derived from baculovirus. The vector pFast- CprME -ZIKV was constructed containing the gene sequences of Zika virus structural proteins and it was used to generate the recombinant bacmids (Bac- CprME -ZIKV) through transformation into DH10BacTM cells. The Bac- CprME -ZIKV was transfected in Spodoptera frugiperda (Sf9) insect cells and batches of BV- CprME -ZIKV were obtained by infection assays using a multiplicity of infection of 2. The Sf9 cells were infected, and the supernatant was collected 96 h post-infection. The expression of the CprME -ZIKV protein on the cell surface could be observed by immunochemical assays. To concentrate and purify virus-like particles, the sucrose and iodixanol gradients were evaluated, and the correct CprME -ZIKV proteins’ conformation was evaluated by the Western blot assay. The virus-like particles were also analyzed and characterized by transmission electron microscopy. Results and discussion: Spherical structures like the native Zika virus from 50 to 65 nm containing the CprME -ZIKV proteins on their surface were observed in micrographs. The results obtained can be useful in the development path for a vaccine candidate against Zika virus.